Analytical Studies in World Music, edited by Michael Tenzer. Oxford: Oxford University Press, 2006. - Kelly Foreman (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2008)
Review of Analytical Studies in World Music